Phylogeography of the New Zealand whelks Cominella maculosa and C. virgata (Gastropoda: Neogastropoda: Buccinoidea: Buccinidae). (21st November 2018) - Walton, Kerry; Marshall, Bruce A; Phillips, Nicole E; Verry, Alexander J F; Ritchie, Peter A
Abstract: Cominella maculosa and C. virgata are common whelk species that inhabit rocky shores around much of the North Island of New Zealand, the northern South Island and, for C. maculosa, the Chatham Islands. This study used DNA sequences from the mitochondrial gene CO1 to examine the phylogeographical structure of populations of both species in areas that have not previously been sampled. Collections of both species were made from sites in the Cook Strait region, C. maculosa from the Chatham Islands and C. virgata from the northern North Island. Both species were found to have a considerable degree of genetic differentiation, but genetic diversity and phylogeographical patterns differed greatly between regions. South Island populations of C. virgata may have originated, or been supplemented, by human-mediated translocations. Phylogenetic analyses were conducted using the mitochondrial genes CO1 and 16S rRNA, and the nuclear gene 18S rRNA. The northern subspecies C. virgata brookesi did not form a monophyletic lineage and is synonymized with C. virgata. A lectotype is designated for Buccinum lineolatum Quoy & Gaimard, 1833, of which C. virgata is a replacement name.